Development and validation of a quantitative questionnaire on the growth of female household heads - Bakhtiar Khalaj, Narjes; Haghighatian, Mansour; Hejazi, Seyed Naser (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The purpose of this research is to identify the native dimensions and components based on the Islamic society and Iranian Muslim women, as well as to identify the native dimensions and components of growth and produce an accurate tool to measure these dimensions. Methods: The research method in this article is Turkish. The statistical population in the qualitative section includes experts and experts in the field of women heads of households. The statistical sample of the qualitative part was 15 people, whose volume was determined by the theoretical saturation method. In the quantitative part, the statistical population was all women heads of households, which was determined by using Cochran's formula to be 384 people, and for more certainty, the statistical sample was increased to 458 people. Results: The results showed that the development of female heads of households has 3 general dimensions (insight, knowledge and character) and 7 factors (faith, self-respect, self-knowledge, knowledge of the environment, life skills, multi-role, behavior management) and the factor load obtained in all Dimensions above 0.70 are acceptable. Conclusion: The growth of women has theoretical and operational complexity and it cannot be claimed that the extracted model is a complete and perfect model, but so far there is no indigenous measurement tool for the growth of female heads of the household, this research can be the first step for research in this field.